Pengaruh Layanan E-Samsat, Samsat Drive Thru, Dan Samsat Keliling Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor: Studi Pada Samsat Bandung III Soekarno-Hatta - Thia Hasibuan; Dyah Purnamasari (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aimed to analyze the influence of E-Samsat, Samsat Drive Thru, and Mobile Samsat services on motor vehicle taxpayer compliance at the Bandung III Soekarno-Hatta Samsat Office. Despite the implementation of service innovations, taxpayer compliance decreased from 78.16% in 2020 to 76.55% in 2024, while vehicles not renewing registration (KTMDU) increased by 32.01%. The study utilized a quantitative research method with primary data collected through questionnaires distributed to 100 respondents selected using simple random sampling from a population of 475,070 registered motor vehicle taxpayers. Data were analyzed using multiple linear regression with classical assumption tests (normality, multicollinearity, and heteroscedasticity) conducted via SPSS version 29. The results indicate that E-Samsat, Samsat Drive-Thru, and Mobile Samsat services have positive and significant partial effects on taxpayer compliance. Based on Standardized Coefficients (Beta), E-Samsat shows the strongest influence (Beta = 0.304), followed by Mobile Samsat (Beta = 0.278) and Samsat Drive-Thru (Beta = 0.211). The model explains 43.5% of the variance in taxpayer compliance (Adjusted R² = 0.435). Practically, these findings are expected to serve as evaluation material for policymakers and Samsat administrators in improving service quality, accessibility, and effectiveness through optimizing digital systems, expanding service coverage, and strengthening service capacity to encourage sustainable motor vehicle taxpayer compliance.